Geometrical modelling of pulsed laser ablation of high performance metallic alloys. (June 2019) - Cha, D.; Axinte, D.; Billingham, J.
Abstract: Modelling of Pulsed Laser Ablation (PLA) for the prediction of complex geometries has generally achieved limited success when aimed at large structures resulting from a high number of overlapped pulses, in particular for the ablation of metallic materials, where a significant volume of molten and re-deposited material can be present. In order to extend the capabilities of process simulation for surface prediction of PLA, this paper presents a novel problem formulation that takes into consideration the behaviour of the ejected/redeposited melt as well as the non-linear interaction between successive pulses when a laser beam is scanned along a given path. This results in a simplified mathematical framework capable of predicting features with good accuracy and low computational cost. The evolution of the depth/height at any point on the surface can be described by the convolution of a radially-varying function that represents the steady state ablation footprint (which includes also material redeposition) created by a pulsed laser scanned across the workpiece scaled according to pulse separation distance (i.e. feed speed). The model also reveals some interesting dynamics of the behaviour of redeposited material, which appears to have a lower removal threshold compared to the virgin material. This can be taken into account in a modified model formulation by introducing a linear scaling coefficient for the ablation function. Validation of the model on Ni- and Ti- superalloy for both the prediction of single trenches (i.e. scanning along straight path) at constant and variable feed speed, and overlapped trenches, is performed with an average error of less than 10%. The framework presented in the paper could provide a valuable step forward in process modelling of PLA for real-world industrial applications. Highlights: Modelling of pulsed laser machining of metallic material which redeposits is performed using a simple approach. The model can be calibrated using a limited number of experimental trials. Features produced from a scanned laser beam can be predicted with an average error of less than 10%. Redeposited material is found to be removed at a faster rate compared to virgin material.